Navigating Digital Borders: Seto Community in the Virtual Territory of the VK Social Network - Ksenya A. Maretina (Changing Societies & Personalities)
The paper examines the digital geography of the virtual Seto community in the VK social network (also known as VKontakte), focusing on how dispersed Seto people in Russia and Estonia use digital spaces to communicate, as well as express, preserve, and promote their cultural identity. By applying a multi-sited ethnographic methodology, the research involves both online explorations and offline semi-structured interviews, with fieldwork conducted in the Pechory District. Using the network and territory approaches to digital ethnography, the study highlights how the VK serves as a digital territory where Setos, divided by distances and physical borders, connect, share cultural practices, and foster a sense of community. Special attention is given to the Seto traditions of leelo polyphonic singing and festive costumes, both of which serve as vital markers of ethnic identity in this digital landscape. Through content analysis of Seto personal profiles and public pages, the research reveals how social networks help maintain connections and how digital geographies are constantly shaped and reshaped by cultural exchanges. This study underscores the adaptability of online spaces in sustaining fragmented ethnic communities across physical distances.